Selection of Aptamers Specific for Adipose Tissue - Liu, Jun (Public Library of Science, 2012)
BACKGROUND: Obesity has reached epidemic proportions, affecting more than one tenth of the world’s population. As such, adipose tissue is being increasingly recognized as an important therapeutic target for obesity and related metabolic disorders. While many potential targets of adipose tissue have been established and drugs developed, very few of those drugs specifically target adipose tissue without affecting other tissue. This results from a limited knowledge of both cell-surface markers and physicochemical traits specific to adipocytes that might otherwise be exploited by circulating drugs. METHODOLOGY/PRINCIPAL FINDINGS: Here we report the use of cell-SELEX technology to select two aptamers that can specifically recognize mature adipocytes: adipo-1 and adipo-8. Adipo-8 shows high affinity for differentiated, mature 3T3-L1 adipocytes with a K(d) value of 17.8±5.1 nM. The binding was sustained upon incubation at 37°C and insulin stimulation, but was lost upon trypsin treatment. The binding ability was also verified on frozen tissue slides with low background fluorescence and isolated adipocytes. CONCLUSIONS/SIGNIFICANCE: Aptamer adipo-8 selected from a random library appears to bind to mature differentiated adipocytes specifically. This aptamer holds great promise as a molecular recognition tool for adipocyte biomarker discovery or for targeted delivery of molecules to adipocytes.